932. Clinical Characteristics of Persistent and Relapsing Babesiosis at an Academic Medical Center in New York City, 2015-2020. (4th December 2021) - Rogers, Wesley; Kirkman, Laura; Simon, Matthew; Westblade, Lars
Abstract: Background: Current guidelines recommend at least 6 weeks of therapy for immunocompromised babesiosis patients; however, limited data exists to guide management in this population. We describe our institutional experience with immunocompromised babesiosis patients. Methods: We reviewed all adult patients reported to the New York City Department of Health and Mental Hygiene with a diagnosis of babesiosis at New York-Presbyterian (NYP)/Weill Cornell Medical Center and NYP/Lower Manhattan Hospital between 2015 and 2020. We compared characteristics and outcomes between patients receiving prolonged treatment (≥ 6 weeks; "cases") and standard treatment (7-10 days; "controls"). Variables were compared using Fishers exact test or Wilcoxon Rank Sum test. Results: Among 35 patients diagnosed with babesiosis, 10 (29%) received at least 6 weeks of therapy. 5/10 (50%) received extended treatment due to persistent and/or relapsing parasitemia, evidence of hemolysis and/or clinical symptoms at 6 weeks from diagnosis (Table 1). The median age was 67 years and immunocompromising conditions included: anti-CD 20 therapy (40%), history of stem cell transplant (20%), anti-TNF alpha (10%), beta-thalassemia (10%), Waldenstrom's macroglobulinemia (10%). Among case patients, the median treatment duration was 53 days (IQR 42-153) and 100% of patients received azithromycin/atovaquone based regimens with adjunctive agents including doxycycline (60%), clindamycin (20%) and proguanil (20%). Compared to control patients, case patients had higher frequency of blood transfusions (50% vs 12%; p =0.03), however, there was no difference in median peak parasitemia (1.13% vs 0.6%), rates of hospital admission (80% vs 88%), length of stay (6 vs 4 days), organ dysfunction (10% vs 4%) and mortality (0% vs 0%) (Table 2). Conclusion: We found a high frequency (29%) of babesiosis patients at our medical center received at least a 6-week treatment course due to immunocompromising conditions. Although immunocompromised patients received longer treatment courses and had more severe anemia, in contrast to prior studies, we found other complications such as hospitalization rates, length of stay, organ dysfunction and mortality were comparable between both patient groups. Disclosures: Lars Westblade, PhD, Accelerate Diagnostics Inc (Grant/Research Support)BioFire Diagnostics (Grant/Research Support)Hardy Diagnostics (Grant/Research Support)Roche (Consultant, Advisor or Review Panel member)Shionogi Inc (Advisor or Review Panel member)Talis Biomedical (Advisor or Review Panel member)